Relative superiority analysis of Garut lamb and its crossbred - Inounu, Ismeth; Hidayati, N; ., Subandriyo; Tiesnamurti, B; Nafiu, L.O (Indonesian Animal Sciences Society, 2003)
The objective of the research was to evaluate the relative superiority of Garut lamb and its crosses with St. Croix and Moulton Charollais. The research was conducted at Animal Research Station, Indonesian Research Institute for Animal Production, Bogor, Indonesia. The data used for this paper was collected from 1995 to 2002. The results revealed that individual lamb weight at birth, at weaning, preweaning daily gain, at 6, 9 and 12 months of age of the composite sheep (HG = 50% St. Croix : 50% Garut, MG = 50% M. Charollais : 50% Garut, MHG (MG X HG) dan HMG (HG X MG) = 25% St. Croix : 25% M. Charollais : 50% Garut) were higher than Garut sheep. The relative superiority were 6.7-13.1% for lamb weight at birth, 6.6- 15.6% for lamb weight at weaning, 3.2-20.8% for preweaning daily gain dan 6.2-17.9% for lamb weight at 9 month of age, respectively. The superiority of composite sheep were obtained in good and limited feed condition. Lamb growth parameters were also affected by feed condition, parity, sex, and rearing type. Â Key words: Garut, St. Croix, M. Charollais sheep, relative superiority